Suppression of microRNA-222-3p ameliorates ulcerative colitis and colitis-associated colorectal cancer to protect against oxidative stress via targeting BRG1 to activate Nrf2/HO-1 signaling pathway - Wang, Xue-jun; Zhang, Dan; Yang, Yan-ting; Li, Xiao-ying; Li, Hong-na; Zhang, Xiao-peng; Long, Jun-yi; Lu, Yun-qiong; Liu, Li; Yang, Guang; Liu, Jie; Hong, Jue; et al. (Frontiers in Immunology, 2023)
Oxidative stress is an important pathogenic factor in ulcerative colitis (UC) and colitis-associated colorectal cancer (CAC), further impairing the entire colon. Intestinal epithelial cells (IECs) are crucial components of innate immunity and play an important role in maintaining intestinal barrier function. Recent studies have indicated that microRNA-222-3p (miR-222-3p) is upregulated in colon of UC and colorectal cancer (CRC) patients, and miR-222-3p is an important regulator of oxidative stress. However, whether miR-222-3p influences IEC oxidative stress in UC and CAC remains unknown. In this study, we investigated the effect of miR-222-3p on the regulation of IEC oxidative stress in UC and CAC. An in vitro inflammation model was established in NCM460 colonic cells, mouse UC and CAC models were established in vivo, and IECs were isolated. The biological role and mechanism of miR-222-3p-mediated oxidative stress in UC and CAC were determined. We demonstrated that miR-222-3p expression was significantly increased in DSS-induced NCM460 cells and IECs from UC and CAC mice. In vitro, the results showed that the downregulation of miR-222-3p reduced oxidative stress, caspase-3 activity, IL-1β and TNF-α in DSS-induced NCM460 cells. We further identified BRG1 as a target gene of miR-222-3p, and downregulating miR-222-3p alleviated DSS-induced oxidative injury by promoting BRG1-mediated activation Nrf2/HO-1 signaling in NCM460 cells. The in vivo results demonstrated that inhibiting miR-222-3p in IECs significantly relieved oxidative stress and inflammation in the damaged colons of UC and CAC mice, as evidenced by decreases in ROS, MDA, IL-1β and TNF-α levels and increases in GSH-Px levels. Our study further demonstrated that inhibiting miR-222-3p in IECs attenuated oxidative damage by targeting BRG1 to activate the Nrf2/HO-1 signaling. In summary, inhibiting miR-222-3p in IECs attenuates oxidative stress by targeting BRG1 to activate the Nrf2/HO-1 signaling pathway, thereby alleviating colonic inflammation and tumorigenesis.